CODE SWITCHING BETWEEN ENGLISH AND JAPANESE IN SONG LYRICS OF THE ALBUM “AMBITION” BY ONE OK ROCK - Kadek Ayu Kartika Septiana; Ni Putu Ayu Kartika Sari Dewi; Ngurah Artha Yoga Pratama; I Wayan Mawa; I Made Suamba; Kadek Agung Sanjaya (Suluh Pendidikan : Jurnal Ilmu-Ilmu Pendidikan, 2024)
This study aims to analyse the use of code-switching in the song lyrics from the album Ambition bythe Japanese band One Ok Rock. Adopting a qualitative research method, this study describes andinterprets the data comprehensively. Sociolinguistics serves as the theoretical framework to investigatethe meanings, types, and functions of code-switching present in the lyrics. The analysis identifiesthree types of code-switching in the album: tag-switching, intra-sentential switching, and intersentential switching. Furthermore, four functions of code-switching are observed: expressive, phatic,metalinguistic, and poetic functions. The findings reveal a total of 34 occurrences of code-switching,consisting of 18 instances categorized by type and 16 instances by function. These results contributeto a deeper understanding of the linguistic strategies employed in the album and their sociolinguisticimplications.